Quantifying the amount of greater brain ischemia protection time with pre-hospital vs. in-hospital neuroprotective agent start - Matossian, Vartan; Starkman, Sidney; Sanossian, Nerses; Stratton, Samuel; Eckstein, Marc; Conwit, Robin; Liebeskind, David S.; Sharma, Latisha; Tenser, May-Kim; Saver, Jeffrey L. (Frontiers in Neurology, 2022)
The objective of this study is to quantify the increase in brain-under-protection time with achieved with prehospital compared with post-arrival start of neuroprotective therapy among patients undergoing endovascular thrombectomy. In order to do this, a comparative analysis was performed of two randomized trials of neuroprotective agents: 1) prehospital strategy: Field Administration of Stroke Therapy-Magnesium (FAST-MAG) Trial; 2) in-hospital strategy: Efficacy and safety of nerinetide for the treatment of acute ischemic stroke (ESCAPE-NA1) Trial. In the FAST-MAG trial, among 1041 acute ischemic stroke patients, 44 were treated with endovascular reperfusion therapy (ERT), including 32 treated with both intravenous thrombolysis and ERT and 12 treated with ERT alone. In the ESCAPE-NA1 trial, among 1105 acute ischemic stroke patients, 659 treated with both intravenous thrombolysis and ERT and 446 treated with ERT alone. Start of neuroprotective agent was sooner after onset with prehospital vs in-hospital start: 45m (IQR 38-56) vs 122m. The neuroprotective agent in FAST-MAG was started 8 minutes prior to ED arrival compared with 64 minutes after arrival in ESCAPE-NA1. Projecting modern endovascular workflows to FAST-MAG, the total time of “brain under protection” (neuroprotective agent start to reperfusion) was greater with prehospital than in-hospital start: 94m (IQR 90-98) vs 22m. Initiating a neuroprotective agent in the prehospital setting enables faster treatment start, yielding 72 minutes longer brain protection time for patients with acute ischemic stroke. These findings provide support for increased performance of ambulance-based, prehospital treatment trials in the development of neuroprotective stroke therapies.